Refleksi Pedagogis John Dewey dalam Praktik PAK Kontemporer: Meninjau Ulang Peran Guru sebagai Fasilitator Pertumbuhan Iman Sesuai Ajaran 1 Korintus 3:6 - Salni Salni; Enjelina Enjelina; Delfiana Putri; Julyanti Napa; Sartika Nipa Patanduk (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This study explores the philosophical and theological implications of John Dewey's pedagogical thought, particularly his emphasis on reflective practice and experiential learning, within the context of Contemporary Christian Religious Education (PAK). Despite its potential to foster active, student-centered learning, a significant gap exists in deeply examining how Dewey's principles align with or challenge PAK's theological aim of faith formation. This qualitative library research, employing Miles and Huberman's data analysis model, addresses this gap by synthesizing Dewey's pedagogical concepts with the Christian theology of spiritual growth, particularly informed by 1 Corinthians 3:6, which posits that God gives the increase. The findings reveal that Dewey's experiential learning framework can profoundly enrich PAK by shifting the teacher's role from a primary knowledge dispenser to a facilitator who guides students in applying biblical truths to real-life experiences. This approach encourages holistic development encompassing cognitive, affective, and psychomotor domains. However, the implementation necessitates a robust theological filter, maintaining that biblical truth is final and acknowledging God's sovereignty in true spiritual growth. The study concludes that while Dewey's pedagogy provides practical strategies for student engagement and character development, its successful integration into PAK hinges on a clear understanding of its theological boundaries, ensuring that pedagogical flexibility is balanced with doctrinal integrity. This research offers a theoretical foundation for transformative PAK practices, aiming to cultivate knowledgeable Christian students with deep and active faith.